PERANAN AIR PERASAN JERUK NIPIS (Citrus aurantifolia) SEBAGAI ANTIMIKROBA TERHADAP Prevotella intermedia PADA PENCEGAHAN PERIIMPLANTITIS (SECARA IN-VITRO) - Akane Kitayama; Calvin Kurnia; Vinna Kurniawati Sugiaman (Universitas Baiturrahmah, 2022)
Introduction: One of the complications of using implants in patients is peri-implantitis which occurs due to the invasion of Prevotella intermedia bacteria. Therefore, we need an agent that can play a role in inhibiting the growth of these bacteria, including lime juice. Lime (Citrus aurantifolia) is an herbal plant that is often used by the community in traditional medicine because it contains antibacterial compounds. The purpose of this study was to determine whether lime juice has antibacterial activity against the growth of Prevotella intermedia by measuring the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC). Method: This research is a laboratory experimental study with a post-test-only control group design approach. The method used in this research is microdilution with 10 treatments. Results: The results of the antibacterial test were carried out by counting the number of bacterial colonies on the agar media, and the data were analyzed by using the One-way ANOVA statistical test. The results showed that the least number of bacterial colonies was found at a concentration of 3.125%, namely 8.75. Conclusion: Lime juice (Citrus aurantifolia) has an antibacterial effect by inhibiting the growth of Prevotella intermedia at a concentration of 3.125% and can kill the growth of Prevotella intermedia at a concentration of 6.25%.